Oesophagobronchial fistula caused by varicella zoster virus in a patient with AIDS: a unique case. Issue 5 (1st May 2002) - Moretti, F; Uberti-Foppa, C; Quiros-Roldan, E; Fanti, L; Lillo, F; Lazzarin, A
Abstract : Human herpesvirus oesophagitis in human immunodeficiency virus positive patients is caused by cytomegalovirus and herpes simplex virus; no cases of oesophagitis and oesophagobrochial fistula as a result of varicella zoster virus (VZV) have been reported to date. This report describes the case of a patient with a 2–3 mm deep oesophageal ulcer whose viral culture was positive for VZV. The patient was treated with acyclovir with resolution of the symptomatology. After the end of the induction treatment, because of the onset of fever and fits of coughing during eating, the patient underwent oesophagography, which showed an ulcer with an oesophagobronchial fistula in the middle and lower third of the oesophagus. This case report stresses the role of VZV infection as a possible cause of oesophagobronchial fistula, a rare but benign condition in patients with AIDS.